Clinical decision‐making and intuition: A task analysis of 44 experienced counsellors. Issue 4 (December 2016) - Fox, Jesse; Hagedorn, W. Bryce; Sivo, Stephen A.
Abstract: Background: Clinical decision‐making and intuition are important concepts to counsellors. However, our understanding of clinical decision‐making and intuition, that is the process whereby clinicians make sound therapeutic judgements, is not well understood and thus is an underrepresented area of research in counselling. Aim: The purpose of this study was to better understand the development of clinical decision‐making and intuition and how it is utilised during therapeutic encounters. Methodology: This study used Q‐Methodology to explore the responses of 44 experienced clinicians to a set of standardised clinical scenarios. Findings: The results suggested that experienced clinicians clustered into a single, common‐factor response, which the researchers assert is the factor of intuition. Implications: The implications from the study's findings include that (a) the study's methodology shows promise for developing more advanced research designs that measure the influence of clinical decision‐making and intuition on client outcomes and (b) the resulting single common factor suggests that experienced clinicians eventually transcend the confines of any single theoretical perspective.